Reinventing public education - Hill, Paul Thomas, 1943-; Rand Corporation; Rand Institute on Education & Training; RAND/University of Washington (UW) Program on Reinventing Public Education; George Gund Foundation; Lilly Endowment (Santa Monica, CA : RAND, 1994)
American public schools have become government institutions, buffeted by political decisions and hamstrung by regulations. This study sought a practical alternative form of governance for public education, and concludes that such an alternative is possible. Public school contracting allows schools to be operated by a variety of public and private organizations, based on school-specific contracts. These contracts would define each school's mission and basis for obtaining public funds and establish standards and procedures for accountability. Local public school boards would not operate schools, but would contract with independent organizations to run them. A local board would oversee many different contracts, some for high schools and some for grade schools, some for highly distinctive schools (e.g., Montessori) and others for more conventional schools. Boards would let contracts to expand or reproduce successful schools, and they could close and replace unsuccessful schools. The report suggests ways school contracting can be tested and implemented. (A more current and expanded version of this book is now available from the University of Chicago Press, 1997, ISBN 0-226-33652-2)
"April 1994."
"Institute on Education and Training."
"This is the first report issued by the Program on Reinventing Public Education, a collaboration between RAND's IET and the University of Washington's Institute for Public Policy and Management"--Preface.
Includes bibliographical references (p. 115-124).
Also available on the internet via WWW in PDF format.
Keywords: Education and state -- United States; Educational accountability -- United States; Educational change -- United States; Educational innovations -- United States; Performance contracts in education -- United States; Privatization in education -- United States; Public schools -- Planning -- United States